Vampires of El Norte [large type] - Cañas, Isabel (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"As the daughter of a rancher in 1840s Mexico, Nena knows a thing or two about monsters--her home has long been threatened by tensions with Anglo settlers from the north. But something more sinister lurks near the ranch at night, something that drains men of their blood and leaves them for dead. Something that once attacked Nena nine years ago. Believing Nena dead, Néstor has been on the run from his grief ever since, moving from ranch to ranch working as a vaquero. But no amount of drink can dispel the night terrors of sharp teeth; no woman can erase his childhood sweetheart from his mind. When the United States invades Mexico in 1846, the two are brought abruptly together on the road to war: Nena as a curandera, a healer striving to prove her worth to her father so that he does not marry her off to a stranger, and Néstor as a member of the auxiliary cavalry of ranchers and vaqueros. But the shock of their reunion--and Nena's rage at Néstor for seemingly abandoning her long ago--is quickly overshadowed by the appearance of a nightmare made flesh. And unless Nena and Néstor work through their past and face the future together, neither will survive to see the dawn" --